Intestinal Lipoma: A Rare Cause of Intestinal Intussusception - Shah, Dr. Harsh R; Borgaonkar, Dr. Vijay; Borgaonkar, Dr. Viraj; Kulkarni, Dr. Pranjal (International Journal of Innovative Research in Medical Science, 2017)
Intussusception is the condition wherein there occurs invagination of one segment of bowel loop in to the adjacent bowel loop. It is an abdominal condition seen commonly among pediatric patients than in adults. Intussusception as a cause for intestinal obstruction is rare in adults and if present it is invariably suspected to be due to an organic pathology, acting as the lead point. Here we are reporting two cases of intestinal intussusception in adult patients, among whom one patient had presented with signs of intestinal obstruction. Their clinical presentation was in the form of abdominal pain, vomiting with or without abdominal distension and/or melena. Both the cases underwent laparotomy, which revealed intussusception and thereby underwent resection and anastomosis of the involved ileal segment. Histopathologically the leading point for the intussusception was a benign mass with features suggestive of a lipoma, submucosal in location. Intestinal submucosal lipoma which often remains as a silent pathology, presenting in the form of lead point for small bowel intussusception in adults is a rare presentation and thereby the need to consider it in the differentials, rather than malignancy as the cause for intussusception.